Breakage of wet flexible fiber agglomerates impacting a plane. Issue 8 (17th May 2019) - Yang, Jiecheng; Bello, Liliana; Buettner, Kevin; Guo, Yu; Wassgren, Carl; Curtis, Jennifer S.
Abstract: The breakage of an agglomerate of wet flexible fibers impacting a plane is computationally investigated in this work using the discrete element method. In the agglomerate, the fibers stick together due to cohesive liquid bridge forces. Agglomerate breakage with various impact conditions, initial configurations, fiber properties, and liquid bridge properties is systematically investigated. The degree of breakage is governed by the impact energy, the cohesion energy due to liquid bridges, the energy dissipation/absorption through fiber–fiber contacts and fiber deformation, and the efficiency of force transmission within the agglomerate. More specifically, breakage is promoted by increasing impact velocity, decreasing agglomerate size, increasing initial compaction, increasing fiber bending modulus, decreasing liquid surface tension, and decreasing liquid‐to‐solid volume ratio. Breakage is strongly dependent on the modified Weber number, that is, the ratio of the Weber number to a dimensionless rupture distance, which is a measure of the impact energy relative to the cohesion energy.